Aplicativo móvil para el aprendizaje de lengua de señas peruanas en la Institución Educativa “Santo Cristo de Bagazán” 2023 - Gutierrez Torres, Neyer (2024)
This research had the purpose to improve the learning of Peruvian Sign Language in secondary students of the I.E. “Santo Cristo de Bagazán” for which The Peruvian Sign Language mobile application called “Manos Unidas” (Joined Hand) was proposed to reduce social gaps regarding people with hearing disabilities. In this context, a mobile application was implemented as a technology alternative that provides a suitable learning methodology in view of the constant use of mobile devices in young people, and it also sought to increase the percentage of students who will be able to dominate basic elements and expressions of Peruvian Sign Language, thus differentiating it from the traditional learning method. The type of research to develop to carry out this project it’s an applicative type since it seeks to improve the problems regarding sign language, for that we proposed the use of a mobile application for learning. Furthermore, the investigation design will be of the quasi experimental type, where it is necessary to indicate that tests will carry out at I.E. “Santo Cristo de Bagazán”, formed by two groups: an experimental group (application method) and a control group (traditional method). Finally, the results obtained demonstrated that there is a significant improvement with the use of the mobile application as learning method, for which it was verified that the average evaluation of basic elements is 17,45 and with respect to basic expressions is 16,51. So, it can be justified that the grades are on the “Excellent” scale.